Dynamics of Implementation of Ppkm Level 4 Policy For Prevention of Covid-19 Transmission in Padang City - Riandini, Ory; Ekha Putera, Roni; Koeswara, Hendri; Alhadi, Zikri (Sumatra Journal of Disaster, Geography and Geography Education, 2022)
This paper discusses the dynamics of implementing the Emergency Community Activity Restriction (PPKM) policy in dealing with the COVID-19 pandemic in the city of Padang, which has been taking place effectively since last July 2021. Several problems arise lack of available resources, weak supervision, and coordination mechanisms that have not been running optimally. However, the implementation of the PPKM policy in Indonesia, including in the city of Padang, has succeeded in reducing the prevalence of Covid 19 virus transmission with all the dynamics it faces. This paper is designed with a qualitative approach, namely by using an analysis of secondary data originating from both print and electronic media as well as a critique of various regulations related to the implementation of PPKM policies both at the national level and at the regional level, especially the City of Padang. The analysis was carried out using the concept of policy implementation as an analytical knife in dissecting the data presented in this paper.